PENGARUH PRAKTIK UNIT BUSINESS CENTRE ALFA TERHADAP MINAT BERWIRAUSAHA SISWA KELAS X BISNIS DARING DAN PEMASARAN SMKN 1 BOJONEGORO DENGAN SELF EFFICACY SEBAGAI VARIABEL INTERVENING - Erina Rahayu; Renny Dwijayanti (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
Abstrack Business center practice is an activity carried out by students regarding sales, service to consumers, to bookkeeping of transactions that have been made. This practice is specifically for class X majoring in online business and marketing with the aim of fostering students' interest in entrepreneurship. With the belief in students so that students are not afraid to try and are motivated to start a business. This research is a descriptive quantitative research, the research method is through questionnaire distribution with a population of all class X students of online business and marketing using a saturated sampling technique with a total of 71 respondents. With path analysis, the results of this study show that business center practices have an effect on self-efficacy, business center practices have had an effect on entrepreneurial interest, entrepreneurial interest has had an effect on self-efficacy and business center practices have had an effect on entrepreneurial intentions with self-efficacy as an intervening variable. . Keywords: business center practice; entrepreneurial interest; self efficacy